2022
DOI: 10.24235/al.ibtida.snj.v9i1.8071
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Internship Program "Merdeka Belajar Kampus Merdeka" Perspectives of Primary School Teachers’ Teaching Readiness

Abstract: The purpose of this study is to analyze the "Merdeka Belajar Kampus Merdeka (MBKM)" program from the perspective of teachers' teaching readiness. The study used a qualitative approach carried out at one elementary school in Wonosobo Regency, Central Java during the early days of learning activities from August to December 2021. Data were collected through observation, interviews, and questionnaires distributed to participants, which included teachers, students, and preservice elementary school teachers of Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It shows that the MBKM program has a positive impact when applied in schools' teaching and learning processes. However, different things are shown in the results of research from Afandi et al [3] in the same year; that is, most of the teachers and students do not yet have the ability to the concept of Merdeka Belajar.…”
Section: Introductionmentioning
confidence: 94%
“…It shows that the MBKM program has a positive impact when applied in schools' teaching and learning processes. However, different things are shown in the results of research from Afandi et al [3] in the same year; that is, most of the teachers and students do not yet have the ability to the concept of Merdeka Belajar.…”
Section: Introductionmentioning
confidence: 94%
“…Several previous research articles on the independent learning program, namely from Afandi and other concluded that in the effectiveness of the independent learning program, children should be given the freedom to play in their learning and will have a good impact on children's character from an early age (Afandi et al, 2022). In line with research Restu and others, The independent learning program is applied experimentally in the classroom to effectively realise that the independent learning program can be more optimal when learning activities occur (Restu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The government was viewed as effective in developing the curriculum, although it was limited in its application (Pratikno et al, 2022). General educators are prepared to administer the Merdeka Curriculum, but with limited comprehension (Afandi et al, 2022). In reality, a solid knowledge of implementation is very necessary for teachers to be successful in the classroom (Maba & Mantra, 2018).…”
Section: Introductionmentioning
confidence: 99%